Is euro area lowflation here to stay? Insights from a time-varying parameter model with survey data - Arnoud Stevens; Joris Wauters (National Bank of Belgium, 2018)
Inflation has been persistently weak in the euro area despite the economic recovery since 2013. We investigate the sources behind this protracted low inflation by building a time-varying parameter model that jointly explains the dynamics of inflation and inflation expectations from the ECB's Survey of Professional Forecasters. We find that the inclusion of survey data strengthens the view that low inflation was mainly due to cyclical drivers. In particular, the model with survey expectations finds a more muted decline of trend inflation in recent years and a larger degree of economic slack. The impact of economic slack and import prices on inflation is found to have increased in recent years. We also find that survey expectations have become less persistent over the financial crisis period, and that including survey data improves the model's out-of-sample forecasting performance.
Keywords: E31; C11; C32; 330; inflation dynamics; trend inflation; survey-based inflation expectations; ECB Survey of Professional Forecasters; nonlinear state space model; Bayesian estimation; euro area